2019
DOI: 10.1016/j.reth.2019.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Second-look arthroscopic findings of cartilage and meniscus repair after injection of adipose-derived regenerative cells in knee osteoarthrits: Report of two cases

Abstract: Background The purpose of this study was to use second-look arthroscopic findings and clinical assessment to determine outcome in two cases of knee osteoarthritis treated by intra-articular knee injection of adipose-derived regenerative cells (ADRCs). Case presentation This study involved two patients who received ADRC therapy for knee osteoarthritis and completed the six-month post-treatment follow-up period. For each treatment, 130 mL of subcutaneous adipose tissue wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Previous clinical studies have shown that implantation of ADRCs could be useful in the treatment of chronic ulcers of the lower limbs [ 11 ], ischemic cardiomyopathy [ 12 ], fat grafting [ 13 ], and limb ischemia [ 14 ]. Moreover, the therapeutic effects of injected non-cultured adipose-derived SVF for treating OA have been investigated in clinical trials, and an improvement in OA symptoms was reported [ 15 , 16 , 17 , 18 ]. While the inhibitory effects of the intra-articular injection of non-cultured adipose-derived SVF on OA progression were suggested in some animal studies [ 19 , 20 ], the effects of human SVF on OA progression and its mechanisms have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous clinical studies have shown that implantation of ADRCs could be useful in the treatment of chronic ulcers of the lower limbs [ 11 ], ischemic cardiomyopathy [ 12 ], fat grafting [ 13 ], and limb ischemia [ 14 ]. Moreover, the therapeutic effects of injected non-cultured adipose-derived SVF for treating OA have been investigated in clinical trials, and an improvement in OA symptoms was reported [ 15 , 16 , 17 , 18 ]. While the inhibitory effects of the intra-articular injection of non-cultured adipose-derived SVF on OA progression were suggested in some animal studies [ 19 , 20 ], the effects of human SVF on OA progression and its mechanisms have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…A recent paper by Onoi et al [111] reported second-look knee arthroscopy findings in two patients after ASC injections. However, only one of the treated patients had a second-look arthroscopy.…”
Section: Stem Cell Injectionmentioning
confidence: 99%
“…MSCs have been widely used as seed cells in meniscus tissue engineering. The repair effect of bone marrow-derived MSCs (BM-MSCs), synovium-derived MSCs (S-MSCs), and adipose-derived MSCs (A-MSCs) have been proved by plenty of studies ( Zellner et al, 2017 ; Onoi et al, 2019 ; Ozeki et al, 2021 ). However, problems such as difficulty obtaining and pain in the donor site may affect their clinical application.…”
Section: Introductionmentioning
confidence: 99%